Glioblastoma in adults: a Society for Neuro-Oncology (SNO) and European Society of Neuro-Oncology (EANO) consensus review on current management and future directions. Issue 8 (24th April 2020) - Wen, Patrick Y; Weller, Michael; Lee, Eudocia Quant; Alexander, Brian M; Barnholtz-Sloan, Jill S; Barthel, Floris P; Batchelor, Tracy T; Bindra, Ranjit S; Chang, Susan M; Chiocca, E Antonio; Cloughesy, Timothy F; DeGroot, John F; et al.
Abstract: Glioblastomas are the most common form of malignant primary brain tumor and an important cause of morbidity and mortality. In recent years there have been important advances in understanding the molecular pathogenesis and biology of these tumors, but this has not translated into significantly improved outcomes for patients. In this consensus review from the Society for Neuro-Oncology (SNO) and the European Association of Neuro-Oncology (EANO), the current management of isocitrate dehydrogenase wildtype ( IDH wt) glioblastomas will be discussed. In addition, novel therapies such as targeted molecular therapies, agents targeting DNA damage response and metabolism, immunotherapies, and viral therapies will be reviewed, as well as the current challenges and future directions for research.